Incorporation of Video Vignettes into Pharmacy Residency Application Processes - Kenric Ware; Jessica Johnson; Hannah Stroud (University of Minnesota Libraries Publishing, 2017)
This commentary discusses the introduction of video vignettes (VVs) into the context of pharmacy residency application processes. An extension of the conversation around which items are requested of pharmacy candidates when applying to pharmacy residency programs is provided. In conjunction with other documents that provide insights into candidates' abilities, video vignettes (VVs) are presented as viable considerations to gain additional perspective. Implications for time-saving and cost conservation by utilizing VVs are also in view. Hiring employees will presumably have the latitude to require the content of VVs to address aspects deemed more relevant to their institutional operating procedures. Foreseeable benefits and challenges to video vignette (VV) adoption are described within this setting. Counterpoints are presented in response to disadvantages to adoption that may surface. An example of a VV has been crafted to actualize sample components that may be feasible for future use. The challenges faced by healthcare facilities to filling pharmacy residency positions from a vast number of applicants remain pronounced. Creativity in the pharmacy residency selection process is often stifled by routinized methods of application review. Innovative models such as VVs could offer a refreshing alternative to candidates for showcasing individualities and perhaps afford evaluating bodies a unique resource for further candidate differentiation.   Type: Commentary